The storm in the barn - Phelan, Matt 1970- (Candlewick Press, 2011)
In Kansas in the year 1937, eleven-year-old Jack Clark faces his share of ordinary challenges: local bullies, his father's failed expectations, a little sister with an eye for trouble. But he also has to deal with the effects of the Dust Bowl, including rising tensions in his small town and the spread of a shadowy illness. Certainly a case of "dust dementia" would explain who (or what) Jack has glimpsed in the Talbot's abandoned barn - a sinister figure with a face like rain. In a land where it never rains, it's hard to trust what you see with your own eyes, and harder still to take heart and be a hero when the time comes
Keywords: Geschichte 1937; Dust Bowl Era, 1931-1939 -- Juvenile fiction; Dürre; Vater; Junge -- 10-11 Jahre; Sandsturm; Kansas; Kansas / Comic books, strips, etc; Dust storms / Fiction; 1931-1939; Graphic novels; Comics (Graphic works); Historical fiction; Comic